Selection according to the complex of economically valuable traits of the crested wheatgrass varieties in the flora of the Kalbinsky Altai and their introduction in the Altai Botanical Garden - Danilova, A.N.; Isakova Е.А.; Sumbembayev А.А. (Fundamental and Experimental Biology, 2022)
The aim of the study is to select Agropyron pectinatum molds from different ecological and geographical places of growth in the natural populations of the Kalbinsky Altai according to a complex of morphological and economically valuable features and their introduction testing in the Altai Botanical Garden. Wild samples of various ecological and geographical origins served as the material for the study. The samples were evaluated during expedition trips on the territory of the Kalbinsky Altai. At the same time, classical methods in geobotany, seed production, and morphology were used. According to the research results, 5 groups of comb-shaped granary associations were evaluated based on a complex of morphological and economically valuable indicators of interest as a source material for creating highly productive pasture and hay lands in the arid regions of the Kazakh Altai. The dominance of morphometric and counting features of aboveground organs of Agropyron pectinatum in all examined associations was found at high and medium levels of variability, rarely at low and occasionally at very high. All the seed samples of Agropyron pectinatum in the culture of the Altai Botanical Garden turned out to be winter-hardy, with a full cycle of seasonal development, medium-flowering, responding to the conditions of culture by increasing the morphometric indicators of terrestrial organs, the mass of 1000 pcs. seeds and yields. Polymorphic and high-yielding 2 cultivated seed samples from the wheat-alfalfa and shrub-wheat associations were selected as promising for inclusion in the second stage of introduction as initial samples for breeding studies.